2004
DOI: 10.1021/jp0474172
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Optical Properties of Silver Nanowire Arrays Embedded in Anodic Alumina Membrane

Abstract: Transparent Ag nanowire arrays embedded in anodic alumina membranes were prepared by a template-based approach combined with ac electrodeposition and subsequent etching of substrate. The optical response of the structure could be attributed to surface plasmon resonance (SPR) of Ag nanowires. When the incident light was perpendicular to the surface of the composite film, only the transverse resonant mode was excited, and a dual peak line shape appeared at about 400 nm in the optical absorption spectrum. The lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
115
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(122 citation statements)
references
References 35 publications
7
115
0
Order By: Relevance
“…In Figure 6a, to clearly compare and emphasize differences, optical absorption curves were normalized with respect to the local maximum corresponding to the green light. The optical absorption peak of AgNRs was shown near around 370 nm (Figure 6a, (i)), which is similar to the reported absorption spectra by Zong et al 20 According to Gan's theory, the optical absorption of AgNRs is associated with geometric factors, especially aspect ratio in which the geometric factors (p) are given by…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…In Figure 6a, to clearly compare and emphasize differences, optical absorption curves were normalized with respect to the local maximum corresponding to the green light. The optical absorption peak of AgNRs was shown near around 370 nm (Figure 6a, (i)), which is similar to the reported absorption spectra by Zong et al 20 According to Gan's theory, the optical absorption of AgNRs is associated with geometric factors, especially aspect ratio in which the geometric factors (p) are given by…”
Section: Resultssupporting
confidence: 86%
“…20 The plasmon resonance wavelength is dependent on the aspect ratio. Zong et al 20 showed that the longitudinal resonance wavelength shifted to a longer wavelength with increasing aspect ratio, whereas the transverse resonance wavelength slightly shifted to shorter wavelength with increasing aspect ratio. Thus, AgNRs plasmonic response can depend on their size, shape, dielectric environment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The absorption bands near 400 and 700 nm are caused by TSPRs and LSPRs of the Ag nanowire array, respectively. 26,27 As the average Ag www.acsnano.org length increases from ϳ380 to ϳ650 nm (the electrodeposition charge Q increases from 200 to 360 mC), the strength of the LSPRs increases about 60%, but the peak position of the LSPRs slightly blue shifts from 727 to 708 nm. This blue shift of LSPRs is mainly caused by the resonances of higher order plasmon modes in the strongly coupled array of Ag nanowires.…”
Section: Resultsmentioning
confidence: 99%
“…Since our silver nanorods are very short at 62 nm, these bands could be assigned simply: the former is due to the transverse mode of the surface plasmon and the latter is due to the longitudinal mode. 32 The transverse mode is slightly red-shifted from approximately 390 to 430 nm when increasing the diameter of silver nanorods from 28 to 51 nm. For example, it is near 430 nm for the nanorods with a 51 nm diameter, while near 390 nm for a 34 nm diameter.…”
Section: Resultsmentioning
confidence: 99%